ANALISIS PERPUTARAN PERSEDIAANDAN PERPUTARAN PIUTANGTERHADAP PROFITABILITAS (Studi Empiris Pada Perusahaan Sektor Makanan DanMinuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016) - Riris Lestiowati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The company had main purpose to maximize profit and having ongoing efforts to a long period of time ) ( going concern .Working capital play significant roles because affect profitability for the company .Working capital component consisting of cash , securities , credit , and supplies .Liquidity is reflected in the ratio of smoothly also has an important role for the company and may affect profitability .The research was done to look at the level of the two , two credit profitability of companies in the food and drink that are listed at the indonesian stock exchange 2014-2016 years .This research is quantitative research .The data used in this research was secondary data such as financial statements . Key Word: account receivable turnover, inventory turnover and profitability